Effectiveness Of Moringa Oleifera And Ginger Extract On The Intensity Of Dysmenorrhea In Adolescent Girls - Nurohmah, Norma; Hannifah, Fanni; Sugesti, Retno (Universitas Tribhuwana Tunggadewi, 2024)
Dysmenorrhea is one of the most common gynecological problems experienced by adolescence girls. Introduction to non-pharmacological treatment of dysmenorrhea in adolescence girls is required to reduce the risks arising from dysmenorrhea with pharmacology that has side effects on the body. Moringa Oleifera and Ginger Extracts are non-pharmacological therapies that have analgesic and anti-inflammatory benefits. To find out the comparison of the effectiveness of Moringa Oleifera and Ginger Extracts against the intensity of dysmenorrhea in adolescent girls. The research methodology was a Study Case Literature Review of dysmenorrhea with the Numeric Rating Scale (NRS) before and after the intervention. There was a decrease in the intensity of dysmenorrhea in the two respondents. The comparison result was that Ginger Extract was more effective (83.3%) than Moringa Oleifera Extract (50%) in reducing the intensity of dysmenorrhea. We expected that Moringa Oleifera and Ginger Extracts could be an alternative in handling both prevention and non-pharmacological treatment of dysmenorrhea.